Geographical and temporal patterns of interstate security competition: Global and regional evidence. (September 2019) - Jakobsen, Jo; Halvorsen, Thomas
This article tests what seems to be a reasonably widespread perception, namely, that the last few years have witnessed intensified interstate security competition in several of the world's regions. Specifically, we investigate whether or not states' military budgets tend to change as a function of changes to the armaments levels of neighbouring states, as the security dilemma model would suggest. We perform two empirical analyses. First, we specify a least square dummy variables model, whose results we map using standard geographic information system software. Our 'hot spot' analysis for the period 2008/2009–2014 suggests that action–reaction dynamics are present in the Middle East, Central and Southern Africa, and the South Caucasus. Neither South nor East or South East Asia is ridden by severe security competition. Europe generally forms a 'cold spot' region, indicating a lower-than-expected level of changes in arms spending. Second, our spatial lag model suggests the presence of action–reaction globally for the whole post-Cold War era, although results are still substantially driven by the last few years. Interstate security competition is now, apparently, an important element of international politics – albeit only in some regions. Our findings also reveal the potential for disarmament spirals.